Utilization of sago (Metroxylon sagu, Rottb.) flour as substitute to wheat in the production of barquillos - Dablo, Angeline P. (2010)
Recent studies show that sago flour can be used to substitute wheat flour in different food processing industries. In this study, one of the goals was to determine the optimum amount of sago flour that will be used in barquillos. Three substitutions were subjected to Preference Ranking Test. The data were calculated using Friedman's Test and results showed that each sample was significantly different from each other, and thus, they were calculated. From the preliminary study 45% sago flour and 60% were not significantly different but the latter was chosen as final product formulation to lower the production cost and for optimum substitution. The final product was subjected to Consumer Acceptability Test using 9-Hedonic Scale. The data was statistically analyzed through Sign Test. The calculated P values for each attribute were less than 0.05, therefore the null hypothesis was rejected and there is sufficient evidence that the final product was within the acceptable range in the quality scale in all attributes. Standardization for cooking and baking time and for the thickness of the product were conducted. The ideal time for cooking the wafer was 70 seconds while for the baking time was 50 minutes. The average thickness of sago barquillos was 1.37 mm. Lastly, proximate analysis was performed to determine the composition present in the food sample. Based on the results, sago barquillos had approximately 3.71% moisture, and the rest as dry basis-1.95% ash, 21.99% crude fat, 0.68%fiber, 14.5% crude protein and 57,13% carbohydrates and therefore can be classified as healthy and nutritious food.